Patient Characteristics and General Practitioners’ Advice to Stop Statins in Oldest-Old Patients: a Survey Study Across 30 Countries - van der Ploeg, Milly A.; Streit, Sven; Achterberg, Wilco P.; Beers, Erna; Bohnen, Arthur M.; Burman, Robert A.; Collins, Claire; Franco, Fabio G.; Biljana Gerasimovska Kitanovska; Gintere, Sandra; Gomez Bravo, Raquel; Hoffmann, Kathryn; et al. (Springer Science and Business Media LLC, 2019)
Statins are widely used to prevent cardiovascular disease (CVD). With advancing age, the risks of statins might outweigh the potential benefits. It is unclear which factors influence general practitioners' (GPs) advice to stop statins in oldest-old patients.